Obraz Hadriana w Historia adversus paganos Orozjusza - Suski, Robert (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
In his History Against the Pagans, Orosius presented Hadrian in a rather positive way, though’ he omit’s the emperor’s Spanish origin. The emperor had a positive attitude toward Christians which is probably why Orosius considered him as a good ruler.
Keywords: historiografia rzymska; antyczne chrześcijaństwo; Cesarstwo Rzymskie